Symmetry-protected hierarchy of anomalous multipole topological band gaps in nonsymmorphic metacrystals - Zhang, Xiujuan; Lin, Zhi-Kang; Wang, Hai-Xiao; Xiong, Zhan; Tian, Yuan; Lu, Ming-Hui; Chen, Yan-Feng; Jiang, Jian-Hua (Nature communications, 2020)
Symmetry and topology are two fundamental aspects of many quantum states of matter. Recently new topological materials, higher-order topological insulators, were discovered, featuring bulk–edge–corner correspondence that goes beyond the conventional topological paradigms. Here we discover experimentally that the nonsymmorphic p 4 g acoustic metacrystals host a symmetry-protected hierarchy of topological multipoles: the lowest band gap has a quantized Wannier dipole and can mimic the quantum spin Hall effect, whereas the second band gap exhibits quadrupole topology with anomalous Wannier bands. Such a topological hierarchy allows us to observe experimentally distinct, multiplexed topological phenomena and to reveal a topological transition triggered by the geometry transition from the p 4 g group to the C 4 v group, which demonstrates elegantly the fundamental interplay between symmetry and topology. Our study demonstrates that classical systems with controllable geometry can serve as powerful simulators for the discovery of novel topological states of matter and their phase transitions. Higher-order topological phenomenologies are usually observed separately, with each system giving rise to a specific type of topological insulator. Here, the authors realise a nonsymmorphic acoustic metacrystal where the first and the second band gap host dipole and quadrupole topology respectively.